2005
DOI: 10.1016/j.crpv.2004.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Implications paléontologiques et géodynamiques de la datation palynologique des sédiments à faciès wealdien de Bernissart (bassin de Mons, Belgique)

Abstract: Rédigé à l'invitation du Comité éditorial RésuméLe para-taxon biorecord Superret-croton, défini par Hughes et al. en 1979 dans le sous-bassin du Wessex (Angleterre), est pour la première fois mis en évidence dans les faciès wealdiens du « cran aux Iguanodons » de Bernissart (formation des Argiles de Sainte-Barbe, bassin de Mons, Belgique). Ce morphotype témoigne de la présence d'angiospermes. Il est équivalent au taxon morphographique Stellatopollis hughesii Penny, 1986. En utilisant son extension verticale dé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The age of P. bernissartensis (Alvin 1957) was reported from the Puits Négresse, Bernissart, Belgium (as Pityostrobus bommeri; Alvin 1953). The Sainte Barbe Formation at Bernissart was recently dated as mid-Barremian to earliest Aptian (Yans et al 2005;range: 127.5-118.5 Ma, midpoint: 123 Ma). For the remaining Wealden taxa (P. corneti, P. heeri, and P. belgica), several recent publications were taken into account to establish an age range of 127.3-89.5 Ma (Robaszynski et al 2001;Yans et al 2005;Quinif et al 2006;Dejax et al 2007).…”
Section: Age Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of P. bernissartensis (Alvin 1957) was reported from the Puits Négresse, Bernissart, Belgium (as Pityostrobus bommeri; Alvin 1953). The Sainte Barbe Formation at Bernissart was recently dated as mid-Barremian to earliest Aptian (Yans et al 2005;range: 127.5-118.5 Ma, midpoint: 123 Ma). For the remaining Wealden taxa (P. corneti, P. heeri, and P. belgica), several recent publications were taken into account to establish an age range of 127.3-89.5 Ma (Robaszynski et al 2001;Yans et al 2005;Quinif et al 2006;Dejax et al 2007).…”
Section: Age Estimationmentioning
confidence: 99%
“…The Sainte Barbe Formation at Bernissart was recently dated as mid-Barremian to earliest Aptian (Yans et al 2005;range: 127.5-118.5 Ma, midpoint: 123 Ma). For the remaining Wealden taxa (P. corneti, P. heeri, and P. belgica), several recent publications were taken into account to establish an age range of 127.3-89.5 Ma (Robaszynski et al 2001;Yans et al 2005;Quinif et al 2006;Dejax et al 2007). However, after the phylogenetic results were considered (see ''Phylogenetic 3 GERNANDT ET AL.-FOSSIL CALIBRATION OF PINACEAE Analysis''), these taxa were ultimately not used for calibration or to apply constraints.…”
Section: Age Estimationmentioning
confidence: 99%
“…Nevertheless, it remains the oldest evidence for trematodes in terrestrial predatory archosaurs (Poinar and Boucot, 2006). Age: The fossil-bearing strata are now more precisely dated to be of Late Barremian to Early Aptian age (Yans et al, 2005;Schnyder et al, 2009;Yans et al, 2012), corresponding with the upper part of magnetochron M1n, M0r and the basal part of M0n. This yields an approximate minimum age for these strata of 125.93 Ma, the age attributed to the top of magnetochron M0r by Ogg (2012), or a more conservative age of 125.7 Ma, the age assigned to the base of the Tethyan Deshayesites deshayesi ammonoid biozone (Schnyder et al, 2009) by Ogg et al (2012).…”
Section: Cretaceous Egg Remains In Terrestrial Archosaur Coprolitesmentioning
confidence: 98%
“…Moreover, recent paleomagnetic and radiometric dating revealed that numerous kaolinitic and ferruginous formations, which classically were ascribed to Tertiary ages, date back to the Lower Cretaceous period. This is the case for the deep kaolinitic profiles on the Hercynian basement in the Belgian Ardenne [ Yans , 2003; Thiry et al , 2006] and also for the siderolothic iron ore deposits in the eastern Paris Basin [ Théveniaut et al , 2007]. Additionally, the Bonherz iron ore deposits in the paleokarsts developed on the Jurassic limestone platform of the Paris Basin also have to been reconsidered as dating to the Cretaceous age, as well as paleokarst deposits in the southern Massif Central [ Thiry et al , 2006].…”
Section: Summary Of Paleomagnetic Datamentioning
confidence: 99%